The Role of Majelis Taklim in Improving People's Understanding of Religion: Peran Majelis Taklim dalam Meningkatkan Pemahaman Agama Masyarakat - Asyraful Khairi; Khairuddin (Academia Open, 2025)
Abstract. General Background: The rapid changes in the modern era have intensified challenges in religious understanding, leaving communities vulnerable to misinterpretations and deviant teachings. Specific Background: In Indonesia, Majelis Taklim functions as an informal Islamic educational forum that plays a vital role in strengthening religious knowledge and fostering community bonds. However, limited research has examined its concrete contributions in rural contexts with specific reference to classical Islamic texts. Knowledge Gap: Previous studies have highlighted the importance of Majelis Taklim in religious education and social development but have not thoroughly investigated the pedagogical methods, contextual challenges, and the depth of its role in shaping community religious understanding. Aims: This study seeks to analyze the role of Majelis Taklim Masjid Raya Al Hafiz in enhancing religious comprehension among the community of Desa Hamparan Perak, focusing on teaching methods, learning outcomes, and encountered obstacles. Results: Findings show that through lectures, dialogue, and kitab kuning–based learning, Majelis Taklim fosters deeper understanding of tauhid, fikih, and tasawuf, while also serving as a forum for spiritual reassurance. Challenges include time constraints, weather conditions, and diverse levels of comprehension. Novelty: This research uniquely integrates classical Islamic texts with contemporary community issues, offering a nuanced perspective on grassroots religious education. Implications: The study underscores Majelis Taklim’s strategic role in cultivating a more religious, harmonious, and resilient society.Highlight : The Majelis Taklim serves as a forum for fostering religious understanding among the community. Teaching focuses on fiqh, tawhid, and tasawuf using classical texts. Challenges include time constraints, weather conditions, and differences in understanding among the congregation. Keywords : Role, Islamic Study Group, Religious Understanding, Community, Village